Pengaruh Math Anxiety Dan Self-Regulation Terhadap Number Sense Mahasiswa Calon Guru - Yuniawatika; Titis Angga Rini; Ibrahim Sani Ali Manggala; Ika Febriana Wati (Universitas Negeri Malang, 2024)
One of the problems with number sense in students occurs due to dependence on modern devices, which weaken sensitivity to numbers and mental calculation abilities. To overcome this degradation, it is necessary to identify the predictors that influence it and develop appropriate teaching strategies in lectures. The aim of this research is to determine the partial and simultaneous influence of math anxiety and self-regulation on students' number sense. This research applies an ex post facto quantitative approach. The research sample involved 334 PGSD UM students obtained through simple random sampling. Data collection instruments include psychological scales for math anxiety and self-regulation variables as well as an essay test for number sense. Data were analyzed using multiple linear regression tests by first fulfilling the classical assumption test. The result is that math anxiety partially has a significant influence on students' number sense. Meanwhile, partial self-regulation does not have a significant influence on students' number sense. Math anxiety and self-regulation simultaneously have a significant influence on PGSD students' number sense.